Inhibitory Effects of Probenecid on Pharmacokinetics of Tenofovir Disoproxil Fumarate and Emtricitabine for On‐Demand HIV Preexposure Prophylaxis. Issue 5 (31st December 2019) - Liu, Stephanie N.; Gufford, Brandon T.; Lu, Jessica Bo Li; Bushman, Lane R.; Anderson, Peter L.; Bergstrom, Richard F.; Desta, Zeruesenay; Gupta, Samir K.
Abstract : In a randomized, crossover pharmacokinetic study in healthy volunteers ( N  = 14), a single dose of 2 g probenecid (PRO)‐boosted 600 mg tenofovir disoproxil fumarate (TDF)/400 mg emtricitabine (FTC) (test (T) +PRO) was compared with the current on‐demand HIV preexposure prophylaxis from the IPERGAY study (a 600 mg TDF/400 mg FTC on day 1 and 300 mg TDF/200 mg FTC on days 2 and 3) (control, C IPERGAY). PRO increased mean single‐dose area under the plasma concentration‐time curve extrapolated to infinity (AUC0–∞, SD ) of tenofovir (TFV) and FTC by 61% and 68%, respectively. The TFV‐diphosphate (TFV‐DP) concentrations in peripheral blood mononuclear cells were higher (~30%) at 24 hours in T +PRO but then fell significantly lower (~40%) at 72 hours compared with C IPERGAY. The interaction between FTC and PRO was unexpected and novel. Further study is needed to determine if this PRO‐boosted TDF/FTC regimen would be clinically effective.